Ear injuries in tertiary care centre, Government General Hospital Kakinada: a comprehensive review - Mummidivarapu, Peter; Ajjada, Bhagya S.; Bandaru, Ramachandra Rao; Vecham, Chandra Sekhar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Objective of the study was to review the presentation, types, and causes of ear injuries and various factors affecting the patients with ear injuries over one year attending Government General Hospital Kakinada. All the patients treated are studied, using their clinical records, and follow-up was made. Data were extracted using Microsoft excel 2010 and statistical package for the social sciences (SSPS) software, the results are presented in simple descriptive and tabular forms. 80 patients, 54 males (67.5%) and 26 females (35.2%) were studied ages 8-74 years with an average of 41±5 years. Road traffic accident (47.5%) was the most common cause of ear injury, followed by self-fall (23.75%) and assault (15%). Ear pain (93.75%) is the most common presenting complaint, followed by bleeding from the ear (71.25%) and hearing loss (35%). External ear injuries are more prone as it is easily accessible it includes lacerations abrasions, hematoma, and avulsion in increasing order, followed by TM perforations. Management and outcomes were good except for a few late presenters with complications.